Security issues and framework of electronic medical record: A review - Jibril Adamu; Raseeda Hamzah; Marshima Mohd Rosli (Bulletin of Electrical Engineering and Informatics, 2020)
The electronic medical record has been more widely accepted due to its unarguable benefits when compared to a paper-based system. As electronic medical record becomes more popular, this raises many security threats against the systems. Common security vulnerabilities, such as weak authentication, cross-site scripting, SQL injection, and cross-site request forgery had been identified in the electronic medical record systems. To achieve the goals of using EMR, attaining security and privacy is extremely important. This study aims to propose a web framework with inbuilt security features that will prevent the common security vulnerabilities in the electronic medical record. The security features of the three most popular and powerful PHP frameworks Laravel, CodeIgniter, and Symfony were reviewed and compared. Based on the results, Laravel is equipped with the security features that electronic medical record currently required. This paper provides descriptions of the proposed conceptual framework that can be adapted to implement secure EMR systems.